ANALYSIS OF COMPRESSIVE STRENGTH OF PAVING BLOCKS WITH THE ADDITION OF WOOD POWDER WASTE AND LIQUID LIME (CACO3) - Fairus Zabadi; Ahmad Fatoni (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
This research was carried out to find out how strong the compressive strength of the Paving Block is to withstand the load above it, by adding sawdust waste and liquid lime (CaCO3). But for Paving Blocks, the effects of adding sawdust waste and liquid lime (CaCO3) are not yet well known. Further research needs to be carried out on the addition of waste sawdust and liquid lime (CaCO3) in making Paving Blocks. The aim of this research is to reduce environmental pollution caused by sawdust waste, and to use this waste as additional construction material technology and to find out how strong the compressive strength of Paving Blocks is so that it can be used as a construction tool. The results of testing the compressive strength of Paving Block aged 7 days in a ratio of 1:5 with the addition of Wood Powder Waste and Liquid Lime (CaCO3), resulted in an average compressive strength of 310.85 Kg/cm2. In a ratio of 1:6 with the addition of Wood Powder Waste and Liquid Lime (CaCO3), an average compressive strength of 241.02 Kg/cm2 was produced. Normal 1:5 Paving Block from 2 samples produces an Average Stress fcr' of 203.62 Kg/cm2 and normal 1:6 Paving Block from 2 samples produces an Average Stress fcr' of 186.08 Kg/cm2. Keywords: Compressive Strength, Paving Block, Wood Powder Waste and Liquid Lime (CaCO3)